PD-1 Blockade in Treatment of NSCLC: A Comprehensive Review of Clinical Efficacy, Safety and Cost-effective - Li, Zeyue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Non-small cell lung cancer, also called NSCLC, makes up 85% incidence in lung cancer, presents a considerable challenge for its high mortality rate and poor prognosis. In recent years, the invention of programmed cell death 1 (PD-1) inhibitor nivolumab, which is a type of immune checkpoint inhibitors, emerging as a groundbreaking drug, has offered a potential solution to tackle the inescapable drawbacks of traditional cancer treatments. Several clinical trials assessing nivolumab's efficacy and safety in the form of monotherapy or combination therapy, demonstrated that nivolumab has remarkably increased the progression-free survival and overall survival for NSCC, in both first- and second-line. Notably, compared to chemotherapy drugs, nivolumab showed a favorable safety profile with fewer immune-related adverse events. Given the high cost and escalating use of nivolumab, finding more cost-effective treatment regimen is imperative. The purpose of this review is to delve into the clinical efficacy and safety of PD-1 inhibitor nivolumab as immunotherapy remedy against NSCLC, providing some therapeutic recommendations for cost-effective. While continued research and development are vital to further enhance nivolumab's potential as a more potent tool to combat cancer.